Karakteristik Beton Dengan Menggunakan Limbah Kaca Sebagai Bahan Penganti Sebagian Pasir - Kadarningsih, Rahmani Kadarningsih; Uwente, Fajar; Utama, Komang Arya; Bahsuan, Rifadli; Usman, Sartika Dewi (Universitas Negeri Gorontalo, 2025)
Glass waste is a non-biodegradable material, so it must be processed or reused. Using glass waste as a substitute for sand in concrete can be an alternative use of glass waste. Furthermore, glass also contains silica (SiO2), which acts as a pozzolan that binds, making it suitable for use as a concrete mixture. The use of glass waste as a sand substitute is crucial for achieving a gradation that meets the requirements. This study used a concrete compression strength of 25 MPa. The percentage of sand substituted by glass waste was 0%, 7.5%, 10%, 12.5%, and 15%. The concrete volumetric weight increased proportionally with the increase in the glass waste percentage. This indicates that the use of glass waste increases the concrete density. This density is correlated with the concrete compressive strength. The results of the test analysis showed that the increase in volumetric weight was proportional to the increase in concrete compressive strength. This indicates that glass waste material has good fine aggregate properties and can be used as a partial sand replacement. This is because the glass waste material has a gradation that meets the requirements and contains silica which has pozzolanic properties so it can bind.